Two new species of Kalyptorhynchia (Koinocystididae and Gnathorhynchidae) from China - Lin, Yi-Tao; Feng, Wei-Tao; Zhuang, Jie-Yi; Zhang, Yu; Wang, An-Tai (Zootaxa, 2017)
Two new species of Kalyptorhynchia (Rhabdocoela), namely Itaipusa sinensis n. sp. (Koinocystididae) and Prognathorhynchus sinensis n. sp. (Gnathorhynchidae) were described from brackish water near Shenzhen Bay, representing the first records of Koinocystididae and Gnathorhynchidae in China. For I. sinensis n. sp., the U-shaped cirrus contains 50 triangular lamellar spines, with two cuticular (pseudocuticular) hooks situated at both sides of its anterior part. The hook I (right side) is funnel-shaped, while the hook II (left side) is triangular lamellar in shape. For P. sinensis n. sp., the proboscis hook has two hooks situated in an anterior to posterior sequence. The semicircular tubular stylet has a hollow spherical dead end posteriorly to the distal opening. Both the morphological and phylogenetic (18S rDNA and 28S rDNA) analyses support the establishment of these two new species.